Occurence of metalresistant microorganisms on islands of the internal shelf of the Antarctic Peninsula - A. B. Tashyrev; P. V. Rokitko; N. A. Matvieieva; A. A. Tashyreva; V. A. Romanovskaya (Ukrainian Antarctic Journal, 2009)
Microorganisms, superresistant to toxic metals, have been revealed in a geographical zone of internal island shelf of Antarctic peninsula (30x60 km) on islands Darboux, Lippmann, Berthelot, Cruls, Barchans, Jalour, Uruguay, Scua, Three pigs, Winter, Grotto, Galindez, Pitermann, Booth, capes Perez, Rasmussen, Tuxen (coast of Antarctic peninsula), and also on distant from them island King-George . The highest number of metalresistant microorganisms is revealed on the medium containing 1000 ppm of Cr(VI) - up to 5,0x105 cells/g of soil and on the medium containing 250 ppm of Ni2+– 3,0-5,0x105 cells/g of soil. Critical concentrations of toxic metals for the Antarctic microorganisms are determined: Hg2+ - 100 ppm, Cu2+ and Ni2+ - 500 ppm, Co2+ - 1000 ppm. For chromium this parameter is higher than 2000 ppm. For the analysis of results of frequency of metalresistant microorganisms occurrence used the factor representativeness (occurrence) Coc suggested by us which allows to characterize in a complex geoobjects since connects two parameters: total of microorganisms and amount metalresistant microorganisms. Factor Coc for nickelresistant and copperresistant microorganisms is practically identical on the investigated geoobjects. High Coc are found out on cape Rasmussen and on island Winter, and the lowest - on island Lippmann. Thereby, we have shown for the first time, that resistance of microorganisms to ultrahigh concentration of toxic metals is widespread phenomenon in soils on an internal island shelf of the Western Antarctic Region. This conclusion is based on: a) superresistancies and polyresistance of the Antarctic microorganisms to toxic metals (Hg2+, Cu2+, Cr(VI), Ni2+, Co2+); b) high frequency of occurrence and high amount of metalresistant microorganisms in the Antarctic soil; c) occurrence of resistant to toxic metals microorganisms in all investigated soil samples in a zone of an internal island shelf of Antarctic peninsula in the extent 30x60 km.